Oncostatin M Suppresses Activation of IL-17/Th17 via SOCS3 Regulation in CD4(+) T Cells - Son, Hye-Jin (J Immunol, 2017)
Oncostatin M (OSM) is a pleiotropic cytokine and a member of the IL-6 family. It has both proinflammatory and anti-inflammatory functions and is involved in the activation of STAT3 and STAT5. Rheumatoid arthritis is an autoimmune disease that causes chronic and excessive inflammation. Rheumatoid arthritis can lead to induction of Th17 cells, which express IL-17. The aim of this study was to measure the effects of OSM on the proliferation of regulatory T cells and Th17 cells from mice. IL-2 immune complex suppressed the development of collagen-induced arthritis in mice and altered the regulatory T/Th17 cell balance by increasing OSM expression. OSM mitigated the proliferation of Th17 cells and decreased the expression of IL-17 and IL-21. It promoted the activation of suppressor of cytokine signaling 3 (SOCS3), STAT3, and STAT5. Inhibition of SOCS3, STAT3, and STAT5 lessened the OSM-induced reduction in proliferation of Th17 cells. These observations suggest that OSM can inhibit Th17 differentiation by reciprocally controlling SOCS3, STAT3, and STAT5.